A core-shell insulin/CS-PLGA nanoparticle for enhancement of oral insulin bioavailability: in vitro and in vivo study. Issue 8 (24th May 2023) - Wu, Jiamin; Chen, Lu; Zhang, Xinyu; Xu, Chunlan; Liu, Junliang; Gu, Jun; Ji, Hangyu; Feng, Xiaojun; Yan, Caifeng; Song, Xiaoli
Abstract: This study aims to prepare a nanodrug system for insulin delivery and controlled release with Poly(lactic acid-glycolic acid) (PLGA) as the shell and polyethylene glycol-chondroitin sulfate as the core to enhance its oral administration bioavailability. The insulin/CS-PLGA nanoparticles (NPs) with an average size of about 150 nm and regular spherical shape were obtained and showed good biocompatibility and relative high drug loading. Insulin can be controlled release according to the environmental pH and retained its original structure. The oral administration of insulin/CS-PLGA NPs showed a relatively higher hypoglycemic effect than that of insulin, indicating the NPs is a potential oral delivery system to enhance insulin bioavailability. Graphical Abstract: UF0001